A love for life - Hancock, Penny (Cambridge English readers. Level 6, 2000)
Fanella bravely faces the challenge of adopting a child alone after her partner leaves her. But then Rod, a teacher who has problems of his own, comes into her life. Fanella has difficult choices and exciting discoveries to make.